O corpo como princípio - Bolognesi, Mário Fernando [UNESP] (Universidade Estadual Paulista, Departamento de Filosofia, 2001)
The raw material of the circus show is the artist's body, as something at times sublime, at times grotesque. The sublime body, on the floor or in the heights, challenges, as a sort of spectacle, the laws of nature. Afterwards, the show is interrupted and the public is invaded by the relaxation and the grotesquerie of the clowns. The circus show thus moves, with ease and mastery, between laughter and death.

A matéria-prima do espetáculo de circo é o corpo do artista, ora sublime, ora grotesco. O corpo sublime, no chão ou nas alturas, desafia, em forma de espetáculo, as leis naturais. No momento seguinte, o espetáculo é interrompido e o público é acometido pela descontração e pelo grotesco dos palhaços. O espetáculo circense, assim, se desloca, com facilidade e maestria, entre o riso e a morte.
The body as principle
Keywords: Circus; clown; laughter; Circo; palhaço; riso